Good Governance Asean Countries With Education Policy In 3 Southern Border Provinces Of Thailand: Yala, Pattani, And Narathiwat - Warisah Wanaeloh (Journal of Social Research, 2024)
Educational management in the three southern border provinces must be arranged following the context of a multicultural society with diversity from other regions of Thailand Because people in the three southern border provinces have different language education from other provinces in Thailand, such as Malay and Arabic, etc. Therefore, this article is essential to those involved in sharing. Find the direction of educational management in the three southern border provinces and educational opportunities that people in the area should receive, both domestically and internationally. The quality of Education in the multicultural society in the three southern border provinces consists of academic achievements according to the curriculum of the Ministry of Education, including people who graduated from abroad can compare their qualifications to work in Thailand. Desirable characteristics and skills in a multicultural society, including education policy in the area with details of Good Governance involved because some people in the area can study abroad. In this regard, one of the elements that are important in the development of sustainable and long-term quality Education in the three southern border provinces is parental participation in education management. Therefore, those involved in education management in the three southern border provinces should seriously and continuously develop the quality of Education there.